Issues in the Contemporary Politics of Sub-Saharan Africa - Harrison, G. author. aut Link
XI, 190 p.
Keywords: Graham Harrison investigates contemporary African politics by privileging the dynamics of political struggle and resistance. Through the analysis of peasant politics, debt and structural adjustment, democratization and identity politics, the author shows the importance of resistance and agency. Detailed studies of Mozambique, Nigeria, and Burkina Faso demonstrate how political organization and resistance have been closely ingrained in particular post-colonial trajectories. An original and refreshing approach to the study of African politics, this will be a useful textbook for upper level undergraduates and postgraduate students.